Nível de atividade física e aptidão física de estudantes do ensino médio da rede pública estadual de escolas de tempo integral e parcial do município de São Luís, Maranhão - OLIVEIRA, Mayara Carvalhal de (2019)
Objective: To evaluate the level of physical activity (NAF) and physical fitness (APF) of students aged 15 to 17 of both genders enrolled in high school in state and full-time public schools in São Luís, MA. Materials and methods: Cross-sectional descriptive correlational epidemiological study with quantitative analysis. Sample of 593 students from the state public high school network; of these, 271 from full schools and 322 from partial schools. 312 females and 281 males. Six schools were visited and data collected in a single moment. In the classroom, a questionnaire containing socioeconomic, environmental, social and physical activity-related questions was applied and anthropometric measurements (weight and height) and a battery of health-related physical fitness tests (flexibility test in the Wells bench, 1-minute abdominal test, dynamometry, 6-minute endurance run and waist circumference Statistical analysis: For normality of continuous quantitative variables, the Kolmogorov-Smirnov test was used. absolute and relative, mean, median, standard deviation (SD), and 95% confidence interval.In association measures, the Chi-square test (X²) was used, followed by Binary Logistic Regression modeling. which presented a p-value of the chi-square test <0.20, were included in the statistical modeling. α error of 5% and β of 10% The statistical package was the SPSS version 23. Results: As age increases, the chances of being physically active decrease by 21%; being male increases the odds of being physically active by 3.6 times; the higher the householder's level of education, the 1% less chance of being physically active; green neighborhoods, plazas, and parks increase the chances of being physically active by 71 percent; Being stimulated by friends decreases the chances of being physically active by 2%. Conclusion: the type of school has no association with the level of physical activity.